Biocidal activity of two essential oils on fungi that cause degradation of paper documents - Borrego, Sofía B (2016)
The aim of this study was to evaluate the biocidal activity of essential oils of Syzygium  aromaticum (L.) Merr. and L. M. Perry (nail) and Allium sativum L. (garlic) against different fungal species producing paper degradation and deterioration. Essential oils (EOs) were obtained from harvested plants in their natural habitat in Cuba, and were tested against the species Aspergillus niger, Aspergillus flavus and Penicillium sp. which were isolated from archival indoor environments and documents with patrimonial value The biocidal activity was studied at different concentrations (70, 50, 25, 12.5 and 7.5%) using the agar diffusion method. The effect of extracts on paper alterations was studied through different techniques including determination of pH and number of copper and scanning electron microscopy (SEM) observations. EOs were analyzed by gas chromatography coupled to mass spectroscopy (GC/MS). The determination of inhibition zones by the agar diffusion method of the tested EOs showed a moderate and/or positive effect. The study of the antifungal activity on paper (?in vivo?) shows that both clove and garlic oils were potent biocides. Although the paper structure was not affected by EOs pure, some molecular damages were observed at lower concentrations across determinations of the pH and copper number.